Públicos domiciliarios para el cobro de la energía dejada de facturar a los usuarios. (2013)
This paper seeks to understand the enactment of Law 142 of 1994 and the relevant rules relating to fraud in the Public Services and for this reason on the basis of legal criteria stated in the jurisprudence of the Constitutional Court consider establishing criteria for which users have brought actions for protection and judges in some failure to establish the power to impose sanctions which have protected the rights invoked by the actors and ordering the companies and the Superintendence of Public Services. The themes provide the source material on the history and practice of the punitive power of the state in public services, to consider the power to impose sanctions in accordance with the provisions of the regulations, a timely reference to the situation of the departments and municipalities in the provision of public services. It should be noted that the focus of competition constitutional sanction from the case law on energy collection and monitoring of public service Superintendent to this problem. In this order, it is essential to consider the descriptive and argumentative part of this research, to recognize the image outside the reality of who have violated their rights. Thus, from a legal perspective and research could be analyzed in order to recognize punitive powers by which operates the constitution and the law.